ANALISIS KESULITAN BELAJAR PESERTA DIDIK MELALUI LKPD BERBASIS LIVE WORKSHEETS PADA MATERI HIMPUNAN DENGAN PENDEKATAN BERBASIS MASALAH - Gina Amanda; Rippi Maya; Risma Amelia (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
Since online learning began to be implemented, many students have difficulty learning, especially in learning mathematics .The purpose of this study is to describe and analyze of student learning difficulties for class VII students through LKPD based on Live Worksheets of SMP Negeri 2 Cikampek and to examine students' constraints when working on the set of worksheets. Worksheets prepared using a problem-based approach (PBL). This research method uses the description method and the research subjects are 45 students in class VII SMP Negeri 2 Cikampek. The data obtained in the form of student answers and analyzed so that conclusions are obtained in the form of research results.The results of this study indicate that grade VII students of SMP Negeri 2 Cikampek can already distinguish between sets and non-sets, but there are still many students who have difficulty writing set notation. Another obstacle is when using Live Worksheets. .These obstacles include the lack of knowledge of students about e-LKPD, lack of confidence/fear of making mistakes when working through Live Worksheets, pressing the finish button incorrectly when completing the worksheet and obstacles from media/mobile phones that do not support the use of Live Worksheets.